Expert qualification in markets for expert services: A Sisyphean Task? - Tim Schneider; Kilian Bizer (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2017)
Moral hazard in expert diagnoses is more complicated in credence goods markets because ex-post verification of service optimality is usually not possible. We provide an experimental framework to investigate expert and consumer behavior as well as market efficiency in a setting in which experts need to invest in costly but unobservable effort to identify consumer problems and consumers are able to visit multiple experts for diagnosis. We introduce heterogeneously-qualified experts, varying in their necessary effort to diagnose consumers. We examine how subjects react to expert qualification and the introduction of price competition. We find that our baseline market is more efficient and qualification is not necessarily the Sisyphean task, as theory predicted. Nevertheless, we observe high skilled experts investing significantly less effort in diagnoses than their low skilled counterparts. Qualifying experts increases efficiency with fixed prices but remains almost without influence in markets with price competition. Introducing price competition does not lead to the predicted market breakdown, but rather has negative effects on market efficiency. In sum, whether expert qualification should be pursued in credence goods markets depends on the market composition and existing institutions.
Keywords: D12; D82; C91; 330; credence goods; expert market; laboratory experiment; expert qualification; second opinions; price competition